2016
DOI: 10.1074/mcp.m115.057232
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Winter-Responsive Proteins in Bread Wheat Using Proteomics Analysis and Virus-Induced Gene Silencing (VIGS)

Abstract: Proteomic approaches were applied to identify protein spots involved in cold responses in wheat. By comparing the differentially accumulated proteins from two cultivars (UC1110 and PI 610750) and their derivatives, as well as the F 10 recombinant inbred line population differing in cold-tolerance, a total of 20 common protein spots representing 16 unique proteins were successfully identified using 2-DE method. Of these, 14 spots had significantly enhanced abundance in the cold-sensitive parental cultivar UC111… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 85 publications
0
44
0
Order By: Relevance
“…The reflector mode was adopted, and peptides were selected in the mass range between 500 and 3500 Da with the resolution set to 50 000 dpi. The peptide mass finger printing (PMF) spectrum, which shows the m/z ( x ‐axis) data of different peptides was compared with the NCBI non‐redundant database of the Mascot search program (Matrix Science, London UK) to identify the proteins in the spots . The parameters are shown in Table .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reflector mode was adopted, and peptides were selected in the mass range between 500 and 3500 Da with the resolution set to 50 000 dpi. The peptide mass finger printing (PMF) spectrum, which shows the m/z ( x ‐axis) data of different peptides was compared with the NCBI non‐redundant database of the Mascot search program (Matrix Science, London UK) to identify the proteins in the spots . The parameters are shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, proteomics studies using techniques such as two‐dimensional electrophoresis (2‐DE) and mass spectrometry (MS) have become popular . Such studies provide an insight into the mechanisms associated with changes in muscle protein quality in shrimp . It has been suggested that proteomics could also be used to identify changes in muscle proteins of shrimp to better understand the pathogenesis of T‐2 …”
Section: Introductionmentioning
confidence: 99%
“…So far, transcriptome and proteome profiles have been investigated in wheat under heat stress, revealing differences in gene expression and protein levels, respectively (Liu et al , 2015; Ahammed and Yu, 2016; Wang et al , 2016 b ; Zhang et al, 2016, 2017; Lu et al , 2017). However, protein post-translational modifications (PTMs) are linked with plant stresses, and reversible protein phosphorylation in particular functions as a crucial regulatory mechanism in many biological processes (Hashiguchi and Komatsu, 2016), including the regulation of abiotic stress signalling in crops (Kline et al , 2010; Bonhomme et al , 2012; Nguyen et al , 2012; Yang et al , 2013; Zhang et al , 2014a, b; Ahammed and Yu, 2016; Zhen et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, these techniques have some disadavantages such as being relatively expensive, time-consuming and laborious [12]. Virus-induced gene silencing (VIGS) is a rapid tool for functional analyses used in different crops and non-model species such as wheat [13], tomato [14] and rye [15]. In addition, this method allows silencing different genes simultaneously in different plant organs like roots and leaves [16][17].…”
Section: Introductionmentioning
confidence: 99%